Gaya Kepemimpinan Situasional Kepala Madrasah dalam Meningkatkan Profesionalisme Guru di MTs Al Iman Gebang Purworejo - Sri Hanik Nihayati (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2019)
Examining the situational leadership style of madrasa principals, especially in increasing the professionalism of teachers at MTs Al Iman Bulus, Gebang Purworejo, who are required to make continuous efforts to improve the quality of their education. This leadership is carried out with a commitment to the Improvement Improvement program carried out by professional teachers in carrying out their duties and responsibilities. The purpose of this study is to describe the implementation of situational leadership of madrasa principals which lead to leadership styles, telling styles, selling styles, participating styles, and delegating styles, as an effort to improve teacher professionalism. This research was conducted using qualitative. The subjects of this study were school principals, teachers and students. Data collection techniques from this study used observation, interviews, and documentation. The results of this study indicate that the head of MTs Al Iman Bulus Gebang Purworejo has implemented a situational leadership style that has fulfilled four indicators. This is evidenced by the results of the research: First, the head of the madrasah has implemented the Telling style as evidenced by 1) giving jobs to teachers providing giving, and not supporting; 2) give directions before doing work. Second, the head of the madrasa has approved the Selling style as evidenced by 1) making clear rules; 2) provide opportunities for teachers to be invited; 3) madrasa principals apply democracy; 4) can accept suggestions from teachers; 5) provide motivation to subordinates in completing work; 6) give praise and incentives to teachers when completing work well. Third, the head of the madrasa has approved the Participating style as evidenced by: 1) the head of the madrasa is able to make decisions in accordance with the completion of work; 2) the madrasa head is active in various activities carried out by the community. Fourth, the madrasa head has implemented the Delegating style, which is evidenced through: 1) the madrasa head renews the work of teachers; 2) the madrasah head gives responsibility to the teacher in completing the work.